The Influence Of The Perception Of The Importance Of Ethics And Social Responsibility On The Ethical Decision Making Of Tax Consultants - Radia, Dewi Andita Permatasari; Utami, Anita Dwi (LPPM Universitas Sebelas April, 2024)
This research aims to determine the influence of the perception of the importance of ethics and social responsibility on the ethical decision making of tax consultants in Tax Consultants registered with the Indonesian Tax Consultants Association (ITCA) Bandung City. The research method uses descriptive quantitative hypotheses with testing using SPSS. The research sample consisted of 227 tax consultants registered with ITCA Bandung City. The research results show that the perception of the importance of ethics and social responsibility influences the ethical decision making of tax consultants. The results of this research show that the role of ethics and social responsibility in the perceptions of official tax consultants can guide them in choosing appropriate actions when faced with an ethical dilemma. Tax consultants in this study have a professional code of ethics which is always used as a guide in acting and behaving.